Implementasi Hukum Dalam Mendukung Usaha Mikro, Kecil, Dan Menengah ( UMKM ) Di Pasar MMTC Medan - Desvita Saragih; Yeni Festriana Manurung; Sindari Br Barus; Hasyim (Fakultas Hukum Universitas Wahid Hasyim, 2024)
Market MMTC Medan is a major trading center in North Sumatra where many Micro, Small, and Medium Enterprises (MSMEs) conduct their business. Micro, Small and Medium Enterprises play an important role in Indonesia's economy, but they face various obstacles, especially related to ineffective law implementation. This research aims to examine in depth the implementation of the law in supporting Micro, Small and Medium Enterprises in Medan's MMTC Market. This research uses a qualitative approach with interview techniques as the data collection method. The results show that despite the positive steps that have been taken, such as the local government's efforts in easing the business licensing process, there are still many Micro, Small and Medium Enterprises that find it difficult to fulfill the licensing requirements. To overcome this problem, it is necessary to increase legal socialization and education through programs that are easily understood by Micro, Small and Medium Enterprises, such as training, workshops, posters, and banners, 55as well as involving community and religious leaders to increase trust and participation. The implication of this study is the need for more effective and comprehensive legal support for Micro, Small and Medium Enterprises, so that they can operate better and improve their competitiveness.